Gut Microbial Dysbiosis Is Associated with Altered Hepatic Functions and Serum Metabolites in Chronic Hepatitis B Patients - Wang, Jing; Wang, Yang; Zhang, Xu; Liu, Jiaqi; Zhang, Qianpeng; Zhao, Yu; Peng, Jinghua; Feng, Qin; Dai, Jianye; Sun, Shujun; Zhao, Yufeng; Zhao, Liping; et al. (Frontiers in Microbiology, 2017)
Chronic hepatitis B (CHB) is a global epidemic disease that results from hepatitis B virus (HBV) infection and may progress to severe liver failure, including liver fibrosis, cirrhosis and hepatocellular carcinoma. Previous evidence has indicated that the dysbiosis of gut microbiota occurs after liver virus infection and is associated with severe liver disease. The aim of this study is to elucidate the compositional and functional characteristics of the gut microbiota in early-stage CHB and to understand their influence on disease progression. We investigated the gut microbial composition of stool samples from 85 CHB patients with low Child-Pugh scores and 22 healthy controls using the Illumina MiSeq sequencing platform. Furthermore, the serum metabolome of 40 subjects was measured by gas chromatography mass spectrometry. Compared with the controls, significant alteration in the gut microbiota was observed in the CHB patients; 5 operational taxonomic units (OTUs) belonging to Actinomyces, Clostridium sensu stricto, unclassified Lachnospiraceae and Megamonas were increased, and 27 belonging to Alistipes, Asaccharobacter, Bacteroides, Butyricimonas, Clostridium IV, Escherichia/Shigella, Parabacteroides, Ruminococcus, unclassified Bacteria, unclassified Clostridiales, Unclassified Coriobacteriaceae, unclassified Enterobacteriaceae, unclassified Lachnospiraceae and unclassified Ruminococcaceae were decreased. The inferred metagenomic information of gut microbiota in CHB showed 21 enriched and 17 depleted KEGG level-2 pathways. Four OTUs, OTU38 (Streptococcus), OTU124 (Veillonella), OTU224 (Streptococcus) and OTU55 (Haemophilus), had high correlations with hosts’ hepatic function indices and 10 serum metabolites, including phenylalanine and tyrosine, which are aromatic amino acids that play pathogenic roles in liver disease. In particular, these 4 OTUs were significantly higher in patients with higher Child-Pugh scores, who also showed diminished phenylalanine and tryptophan metabolisms in the inferred gut metagenomic functions. These compositional and functional changes in the gut microbiota in early-stage CHB patients suggest the potential contributions of gut microbiota to the progression of CHB, and thus provide new insight into gut microbiota-targeted interventions to improve the prognosis of this disease.